Water hardness test paper and preparation method thereof
By using a mixed solution of 1-aminoanthraquinone-2-sulfonate sodium salt, disodium EDTA and magnesium sulfate to impregnate the test strips, the problem of low sensitivity of existing water hardness detection test strips is solved, and the accuracy of the hardness of low concentration water samples is achieved Detection and clear resolution, suitable for a variety of water quality testing applications.
Patent Information
- Application Number
- CN202411225997.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2025-01-10
AI Technical Summary
The existing water hardness detection test strips have low sensitivity, especially when measuring low-concentration water samples, the color change of the traditional reaction substrate chrome black T is not obvious enough, resulting in inaccurate measurement.
The test strip matrix was impregnated with a mixture of 1-aminoanthraquinone-2-sulfonate sodium salt as the reaction substrate and a mixed solution of EDTA disodium and magnesium sulfate. The complex with significant color difference was generated through specific reactions, which enhanced the detection sensitivity and added pH stabilizers, antioxidants or surfactants to improve the performance of the test strip.
It achieves clear and clear definition of different water samples hardness, improves measurement accuracy and sensitivity, and is suitable for various water quality detection scenarios, including rapid detection of industrial and domestic water.
Smart Images

Figure CN119290855A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of environmental detection and food detection, and relates to a water hardness test paper and a preparation method thereof, in particular to a water hardness test paper with clear color scale and a preparation method thereof. Background Art
[0002] Water is the most abundant substance in the world. About 3 / 4 of the earth's surface is covered by water. Water has a very close relationship with human production and life. Natural water sources can be divided into two categories: surface water and groundwater. Surface water mainly comes from rainwater, including river water, lake water, sea water, etc.; groundwater is formed by surface water seeping into the ground. Obviously, the composition and content of impurities contained in natural water are very complex. Water quality is the abbreviation of water quality, which indicates the physical, chemical and biological characteristics and composition of water. Different uses of water have different requirements for water quality. For this reason, the state has issued a series of documents such as "Surface Water Environmental Quality Standard" (GB3838-2002), "Comprehensive Sewage Discharge Standard" (GB8978-1996) and "Sanitary Standard for Drinking Water" to stipulate the corresponding water quality standards in different application occasions. The current implementation standard for the water quality requirements of industrial boiler water in my country is the "Industrial Boiler Water Quality" (GB1576-2001) promulgated by the State Administration of Quality and Technical Supervision. This standard is based on the experience gained since the implementation of the "Low-pressure Boiler Water Quality" (1576-1996) and its inadaptability to the environment. It has been modified and improved accordingly to better meet the actual production requirements. Detailed quantitative regulations have been made for various indicators of boiler water such as rated steam pressure, suspended matter, total hardness, total alkalinity, pH, dissolved oxygen, etc. Among the above-mentioned indicators, water hardness is a more critical parameter. It is of great necessity and practical value to be able to accurately, quickly and conveniently measure the hardness value of boiler feed water.
[0003] Natural water contains certain metal ions to varying degrees, and these ions are generally Ca 2+ Mg 2+ The content of ions is the highest. "Water hardness" refers to the amount of Ca in water. 2+ Mg 2+ Ion content (concentration). When water is heated, Ca 2+ Mg 2+The solubility of ions in water is reduced, and solid attachments composed of calcium carbonate and magnesium hydroxide will form on the heating surface, which is what we usually call "scale". We generally do not pay too much attention to scale in daily life, but if the hardness of boiler water is too high for a long time and scale is formed, it will bring very serious consequences. The scale layer formed on the inner wall of the boiler and the inner wall of the pipe where hot water and steam flow will hinder heat conduction, affect the working efficiency of the entire system, and increase the operating cost of the boiler; in severe cases, it will cause deformation and cracks of the boiler and the pipe, cause explosion accidents, and threaten the safety of workers' lives and property. Therefore, it is necessary to develop a monitoring instrument to detect the hardness of water flowing into boilers, steam drums and other devices online. When the concentration of calcium and magnesium ions in the water exceeds the predetermined standard, the detection instrument should alarm in time and notify the staff to carry out necessary treatment. The water hardness measuring device can effectively prevent the formation of scale, improve the service life of the boiler and the degree of automation of industrial production, fundamentally ensure the safe and economical operation of the boiler, and also provide a safer and more relaxed working environment for the staff.
[0004] If the hardness of domestic and drinking water is too high, it is easy to have adverse effects on human health. Therefore, there are certain requirements for the water source for domestic and drinking water. At present, civilian water purifiers have also become popular. Usually in life, especially for maternal and infant products, water purifiers also have the function of removing ions. The hardness value is an important indicator for testing the water purification effect of water purifiers. Using test paper to quickly test the hardness of water can also allow consumers to judge the water purification effect of water purifiers with the most intuitive feeling. Therefore, test paper for water hardness detection has a certain market.
[0005] Some water hardness test paper products on the market (such as CN1185487C, CN1588008A, etc.) have low sensitivity, and different concentration levels are all dark blue, and the color difference is not obvious enough. When measuring soft water with low hardness, it is impossible to distinguish below 100ppm. The main reason is that the reaction substrate used in traditional hardness test paper is chrome black T, and the color change before and after the complexation with calcium and magnesium ions is not obvious enough, so the sensitivity is low. Summary of the invention
[0006] The purpose of the present invention is to provide a water hardness test paper with clear color levels and a preparation method thereof, which has the advantages of accurate concentration indication, high sensitivity, simple operation, fast testing speed, and high safety of the test paper to the human body. In particular, when measuring soft water with a low hardness value, the color levels of water samples with different hardness values are clear. It can be applied to industries such as fishery breeding, agriculture, environmental testing, food testing, and scenes for rapid detection of water hardness in daily life.
[0007] The purpose of the present invention can be achieved by the following technical solutions:
[0008] The first aspect of the present invention provides a method for preparing a water hardness test paper, comprising: preparing a mixed solution containing 1-aminoanthraquinone-2-sulfonic acid sodium salt, disodium EDTA, and magnesium sulfate, impregnating a test paper substrate, and drying to obtain the water hardness test paper.
[0009] The test paper detection principle of the present invention is: 1-aminoanthraquinone-2-sulfonic acid sodium salt is used as a reaction substrate, which can specifically react with calcium ions and magnesium ions in water to generate a complex with a different color from the original substrate, thereby indicating the concentration of calcium and magnesium ions in water. The color difference varies greatly with the concentration, which is convenient for comparing and reading the hardness level. Disodium EDTA and magnesium sulfate are used as sensitizers to improve the sensitivity of the test paper detection.
[0010] Furthermore, the mass ratio of the 1-aminoanthraquinone-2-sulfonic acid sodium salt, disodium EDTA, and magnesium sulfate is (0.08-0.15):(0.40-0.60):(0.05-0.15).
[0011] Furthermore, the mass concentration of the disodium EDTA in the mixed solution is 0.2-2.0%, and / or the mass concentration of the magnesium sulfate in the mixed solution is 0.04-4.0%.
[0012] Furthermore, during the impregnation process, the impregnation temperature is room temperature and the impregnation time is 10-60s.
[0013] Furthermore, the drying is carried out under reduced pressure, the drying temperature is 25-40° C., and the vacuum degree is 0.1-20 Pa.
[0014] Furthermore, the mixed solution also includes at least one of a pH stabilizer, an antioxidant or a surfactant.
[0015] Furthermore, the pH stabilizer is potassium hydrogen phthalate, the mass concentration of which in the mixed solution is 0.8-1.2%, and the pH of the mixed solution is 4-4.5.
[0016] Furthermore, the antioxidant is sodium ascorbate, and the mass concentration of the antioxidant in the mixed solution is 0.1-2.0%.
[0017] Furthermore, the surfactant is hexadecyl ammonium bromide, and its mass concentration in the mixed solution is 0.05-0.5%.
[0018] Furthermore, the test paper matrix is a chromatography-grade filter paper that does not contain calcium and magnesium ions.
[0019] Furthermore, the solvent of the mixed solution is water or a mixture of water and ethanol. Preferably, the solvent is an ethanol aqueous solution with an ethanol volume content of 50%.
[0020] The second aspect of the present invention provides a water hardness test paper product, including a test paper substrate, and a test paper detection base layer and a hand-holding area arranged on the test paper substrate, wherein the detection base layer is a water hardness test paper prepared by the method described above.
[0021] Furthermore, the test paper substrate is a PET substrate or a PVC substrate.
[0022] When in use, the water hardness test paper or test paper product can be immersed in the solution to be tested and then taken out, excess test solution can be removed, and the hardness of the test solution can be read after standing by comparing the color with the colorimetric card.
[0023] Preferably, the immersion time of the solution to be tested is not less than 5 s, and the immersion time is not less than 30 s.
[0024] Compared with the prior art, the present invention has the following characteristics:
[0025] 1) The present invention does not require a specific environment and professional operating skills, can achieve rapid detection, and is easy to use; the amount of test reagents used is less than that used in laboratory methods, saving test costs; the test paper substrate includes a hand-held area, which enables the operator to avoid reagent contamination when taking the test paper and testing, and is widely applicable to various water quality detection scenarios;
[0026] 2) The production process of the present invention is reasonable, the raw materials used are easy to obtain, the equipment cost is low, and batch production can be carried out. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a structural schematic diagram of a water hardness test paper product with clear color scale in the present invention;
[0028] Figure 2 This is a diagram showing the color development effect of a hardness test paper prepared in Example 2 on different hardness standard solutions;
[0029] Description of the markings in the figure:
[0030] 1-test paper detection base layer, 2-test paper substrate, 3-hand-held area. DETAILED DESCRIPTION
[0031] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0032] Unless otherwise specified, the following implementation processes were all carried out at room temperature.
[0033] Prepare calcium standard solutions of different concentrations (1800mg / L, 1200mg / L, 300mg / L, 180mg / L, 120mg / L, 60mg / L, 30mg / L) with calcium carbonate, concentrated hydrochloric acid and pure water. The calcium carbonate used is the reference material. Weigh 4.50g calcium carbonate and 3.00g calcium carbonate respectively and place them in two 1000mL volumetric flasks, add 50mL pure water, then drip concentrated hydrochloric acid until the calcium carbonate is completely dissolved, add 100mL water after dissolution, adjust the pH value to between 6.0-7.0 with 0.1mol / L sodium hydroxide, dilute with water to the scale, mix well, and obtain 1800mg / L calcium standard solution and 1200mg / L calcium standard solution. Pipette 25mL of 1200mg / L calcium standard solution in a 1000mL volumetric flask and dilute with water to the scale, mix well, and obtain 300mg / L calcium standard solution. Pipette 10mL of 1800mg / L calcium standard solution into a 100mL volumetric flask and dilute to the mark with water, mix well, and you will get a 180mg / L standard solution. Pipette 10mL of 1200mg / L calcium standard solution into a 100mL volumetric flask and dilute to the mark with water, mix well, and you will get a 120mg / L standard solution. Pipette 5mL of 1200mg / L calcium standard solution into a 100mL volumetric flask and dilute to the mark with water, mix well, and you will get a 60mg / L standard solution. Pipette 10mL of 300mg / L calcium standard solution into a 100mL volumetric flask and dilute to the mark with water, mix well, and you will get a 30mg / L standard solution.
[0034] The filter paper in the following embodiments is commercially available chromatography grade paper chromatography filter paper. In a more preferred embodiment, a special chromatography grade paper chromatography filter paper in which calcium and magnesium ions are strictly controlled (more preferably, free of calcium and magnesium ions) during the filter paper production process can be selected.
[0035] Example 1
[0036] A water hardness test paper, the preparation method of which comprises:
[0037] Weigh 0.08g of 1-aminoanthraquinone-2-sulfonic acid sodium salt, 0.50g of disodium EDTA and 0.10g of magnesium sulfate, add 100mL of pure water, stir until all the solids are dissolved, immerse the filter paper in the solution, take out the filter paper after 10 seconds, and place it in an oven at 40°C under vacuum and dry for 80 minutes to obtain water hardness test paper that meets the requirements.
[0038] Cut the water hardness test paper into strips of 0.5cm*20cm, paste them on one side of the test paper substrate 2 made of PVC material to form the test paper detection base layer 1, and then cut them in units of 0.5cm width to finally obtain a water hardness test paper product with a size of 0.5cm*0.5cm. The structure is as follows Figure 1As shown, it includes a test paper substrate 2, a hand-held area 3 arranged on one side thereof and a test paper detection base layer 1 pasted on the other side.
[0039] The test paper prepared in Example 1 was immersed in calcium standard solutions of different concentrations for 5 seconds, then taken out and the excess solution was shaken off. The test paper was placed horizontally upward for 30 seconds, and then a standard color card with consistent color tone was made using Adobe Illustrator CS6 software according to the color of the test paper. Figure 2 shown.
[0040] The hardness test paper product with chrome black T as the indicator purchased on the market from Shanghai Xinsheng Test Chemical Technology Co., Ltd. was tested and compared with the test paper of this embodiment. The results are as follows: the lowest detection line of the test paper of this embodiment can reach 30ppm, while the lowest detection line of the test paper with chrome black T as the indicator is only 50ppm; the colorimetric card readings of the test paper of this embodiment are 30, 60, 120, 180, and 300ppm, and the test linearity is good, while the colorimetric card readings of the test paper with chrome black T as the indicator are 50, 100, 250, 500, and 1000ppm, and the sensitivity and linearity results are worse than those of the test paper of this embodiment.
[0041] Example 2
[0042] A water hardness test paper, the preparation method of which is different from that of Example 1 only in that:
[0043] Weigh 0.08g of 1-aminoanthraquinone-2-sulfonic acid sodium salt, 0.50g of disodium EDTA, 0.10g of magnesium sulfate, and 1.0g of potassium hydrogen phthalate, add 100mL of pure water, stir until all the solids are dissolved, and then adjust the pH value to between 4.0 and 4.5 with 0.1mol / L sodium hydroxide solution. Immerse the filter paper in the solution, take out the filter paper after 10 seconds, and place it in an oven at 40°C for vacuum drying for 80 minutes to obtain a water hardness test paper that meets the requirements.
[0044] The rest is the same as in Example 1.
[0045] After adding potassium hydrogen phthalate and sodium hydroxide, the anti-interference ability is enhanced when testing sample solutions with different pH values. Take 100mL of 180mg / L standard solution and add 0.01mol / L hydrochloric acid solution and 0.01mol / L sodium hydroxide solution to prepare 3 sample solutions with different pH values, and the pH values of the sample solutions are 4.5, 6.5, and 8.0 respectively. The test paper described in Example 1 and the test paper described in Example 2 were used to detect the sample solutions respectively. The comparison results showed that the color development of the test paper of Example 1 for the alkaline sample solution of pH 8.0 was biased, and the reading was 120ppm, while Example 2 had no effect.
[0046] Example 3
[0047] A water hardness test paper, the preparation method of which is different from that of Example 1 only in that:
[0048] Weigh 0.10g of 1-aminoanthraquinone-2-sulfonic acid sodium salt, 0.50g of disodium EDTA, 0.10g of magnesium sulfate, and 1.0g of potassium hydrogen phthalate, add 100mL of pure water, stir until all the solids are dissolved, and then adjust the pH value to between 4.0 and 4.5 with 0.1mol / L sodium hydroxide solution. Immerse the filter paper in the solution, take out the filter paper after 10 seconds, and place it in an oven at 40°C for vacuum drying for 80 minutes to obtain a water hardness test paper that meets the requirements.
[0049] The rest is the same as in Example 1.
[0050] Compared with Example 2, increasing the usage of 1-aminoanthraquinone-2-sulfonic acid sodium salt has substantially no effect on the test paper.
[0051] Example 4
[0052] A water hardness test paper, the preparation method of which is different from that of Example 1 only in that:
[0053] Weigh 0.15g of 1-aminoanthraquinone-2-sulfonic acid sodium salt, 0.50g of disodium EDTA, 0.10g of magnesium sulfate, and 1.0g of potassium hydrogen phthalate, add 100mL of pure water, stir until all the solids are dissolved, and then adjust the pH value to between 4.0 and 4.5 with 0.1mol / L sodium hydroxide solution. Immerse the filter paper in the solution, take out the filter paper after 10 seconds, and place it in an oven at 40°C for vacuum drying for 80 minutes to obtain a water hardness test paper that meets the requirements.
[0054] The rest is the same as in Example 1.
[0055] Comparing Example 2 with Example 3, further increasing the usage of 1-aminoanthraquinone-2-sulfonic acid sodium salt slightly improves the sensitivity of the test paper.
[0056] Example 5
[0057] A water hardness test paper, the preparation method of which is different from that of Example 1 only in that:
[0058] Weigh 0.15g of 1-aminoanthraquinone-2-sulfonic acid sodium salt, 0.50g of disodium EDTA, 0.10g of magnesium sulfate, 1.0g of potassium hydrogen phthalate, and 0.10g of sodium ascorbate, add 100mL of pure water, stir until all solids are dissolved, and then adjust the pH value to between 4.0 and 4.5 with 0.1mol / L sodium hydroxide solution. Immerse the filter paper in the solution, take out the filter paper after 10 seconds, and place it in an oven at 40°C for vacuum drying for 80 minutes to obtain a water hardness test paper that meets the requirements.
[0059] The rest is the same as in Example 1.
[0060] The test paper described in Example 2 and the test paper described in Example 5 were exposed to air at the same time and placed in a constant temperature and humidity chamber at a temperature of 60±5°C and a humidity of 75±5%RH. After one week, the results of the two test papers detecting the sample solution were compared. The concentrations of the sample solutions were 60mg / L, 120mg / L, and 180mg / L, respectively. When the test paper described in Example 2 detected the sample solution, the color became lighter and the test paper failed, while Example 5 had no effect. The stability of the test paper described in Example 5 is better than that of Example 2.
[0061] Example 6
[0062] A water hardness test paper, the preparation method of which is different from that of Example 1 only in that:
[0063] Weigh 0.15g of 1-aminoanthraquinone-2-sulfonic acid sodium salt, 0.50g of disodium EDTA, 0.10g of magnesium sulfate, 1.0g of potassium hydrogen phthalate, and 0.20g of sodium ascorbate, add 100mL of pure water, stir until all solids are dissolved, and then adjust the pH value to between 4.0 and 4.5 with 0.1mol / L sodium hydroxide solution. Immerse the filter paper in the solution, take out the filter paper after 10 seconds, and place it in an oven at 40°C for vacuum drying for 80 minutes to obtain a water hardness test paper that meets the requirements.
[0064] The rest is the same as in Example 1.
[0065] The stability experiment was extended to 1 month. Compared with Example 5, the appearance color of Example 5 was dark gray, while the appearance color of the test paper of this example remained basically unchanged, indicating that increasing the amount of sodium ascorbate in this example can enhance the stability of the test paper.
[0066] Example 7
[0067] A water hardness test paper, the preparation method of which is different from that of Example 1 only in that:
[0068] Weigh 0.15g 1-aminoanthraquinone-2-sulfonic acid sodium salt, 0.50g disodium EDTA, 0.10g magnesium sulfate, 1.0g potassium hydrogen phthalate, 0.10g sodium ascorbate, 0.05g hexadecyl ammonium bromide, add 100mL pure water, stir until all solids are dissolved, and then adjust the pH value to between 4.0 and 4.5 with 0.1mol / L sodium hydroxide solution. Immerse the filter paper in the solution, take out the filter paper after 10 seconds, and place it in an oven at 40°C for vacuum drying for 80 minutes to obtain a water hardness test paper that meets the requirements.
[0069] The rest is the same as in Example 1.
[0070] The test papers of Example 5 and Example 7 were placed on the culture medium at the same time, placed in a constant temperature and humidity chamber at 37°C and 85%RH, and taken out after 72 hours. The surface of the test paper was observed, and it was found that the test paper of Example 5 had mildew spots on the surface, while the test paper of Example 7 did not, indicating that hexadecyl ammonium bromide can effectively prevent mildew.
[0071] Example 8
[0072] A water hardness test paper, the preparation method of which is different from that of Example 1 only in that:
[0073] Weigh 0.15g of 1-aminoanthraquinone-2-sulfonic acid sodium salt, 0.50g of disodium EDTA, 0.10g of magnesium sulfate, 1.0g of potassium hydrogen phthalate, 0.10g of sodium ascorbate, and 0.05g of hexadecyl ammonium bromide, add 100mL of ethanol aqueous solution (ethanol: water v:v = 50:50), stir until all solids are dissolved, and then adjust the pH value to between 4.0 and 4.5 with 0.1mol / L sodium hydroxide solution. Immerse the filter paper in the solution, take out the filter paper after 10 seconds, and place it in an oven at 40°C for vacuum drying for 80 minutes to obtain a water hardness test paper that meets the requirements.
[0074] The rest is the same as in Example 1.
[0075] Compared with Example 7, the results of the detection of the standard solution in this example are consistent with the results of the detection of the standard solution in Example 7, indicating that using pure water and using 50% ethanol aqueous solution as solvent has no effect on the test paper.
[0076] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for preparing a water hardness test paper, characterized in that: include: A mixed solution containing 1-aminoanthraquinone-2-sulfonic acid sodium salt, disodium EDTA and magnesium sulfate is prepared, and the test paper substrate is impregnated with the solution, and the solution is dried to obtain the water hardness test paper.
2. The method for preparing water hardness test paper according to claim 1, characterized in that: The mass ratio of the 1-aminoanthraquinone-2-sulfonic acid sodium salt, disodium EDTA and magnesium sulfate is (0.08-0.15):(0.40-0.60):(0.05-0.15).
3. The preparation method of water hardness test paper according to claim 2, characterized in that, The mass concentration of the disodium EDTA in the mixed solution is 0.2-2.0%, and / or the mass concentration of the magnesium sulfate in the mixed solution is 0.04-4.0%.
4. The preparation method of water hardness test paper according to claim 1, characterized in that, During the impregnation process, the impregnation temperature is room temperature and the impregnation time is 10-60s.
5. The preparation method of water hardness test paper according to claim 1, characterized in that, The drying is carried out under reduced pressure, the drying temperature is 25-40° C., and the vacuum degree is 0.1-20 Pa.
6. The method for preparing water hardness test paper according to claim 1, characterized in that: The mixed solution also includes at least one of a pH stabilizer, an antioxidant or a surfactant.
7. The method for preparing the water hardness test paper according to claim 6, characterized in that: The pH stabilizer is potassium hydrogen phthalate, the mass concentration of which in the mixed solution is 0.8-1.2%, and the pH of the mixed solution is 4-4.
5.
8. The method for preparing water hardness test paper according to claim 6, characterized in that: The antioxidant is sodium ascorbate, and the mass concentration of the antioxidant in the mixed solution is 0.1-2.0%.
9. The method for preparing the water hardness test paper according to claim 6, characterized in that: The surfactant is hexadecyl ammonium bromide, and its mass concentration in the mixed solution is 0.05-0.5%.
10. A water hardness test paper product, characterized in that: The invention comprises a test paper substrate (2), and a test paper detection base layer (1) and a hand-held area (3) arranged on the test paper substrate (2), wherein the detection base layer (1) is a water hardness test paper prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Test paper for detecting total hardness of water and its prepn process
CN1185487C
Test paper for detecting water hardness and detecting method
CN1588008A